Statistické hodnocení regionálních charakteristikvztah mezi mírou kapitálové síly a hrubým domácím produktem - Kraftová, Ivana (Univerzita Pardubice, 2000)
Another part of the capital potencial of a region as a great factor of the regional wealth is dealt with in the contribution. It defines the characteristic of the capital potential of a region derived from the fixed capital supply, employment (the number of employees) in the branch where republic and regional figures are combined. In the end there is a regressional model set as well as counted regions of variability and close dependance. The moel shows high cofficient of determination between regional GDP and capital potential of a region.
Keywords: regionální ekonomika; výkonnost; hrubý domácí produkt; kapitál